ANALISIS PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU DENGAN KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI VARIABEL MODERASI (Studi Kasus GURU TK ABA KOTA SEMARANG) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research aims to test and analyze the influence of discipline and motivation on teacher performance with moderation principal’s leadership at ABA Kindergarten teachers Semarang. The results showed that; (1) Discipline has positive  significant impact on teacher performance (2). Motivation has positive and significant effect on the performance; (3) the principal's leadership does not have positive and significant effect on the performance of the teacher; (4) the leadership of the Principal does not moderate the influence of discipline on teacher performance; (5) the leadership of the Principal does not moderate the effect of motivation on teacher performance;   Keywords : discipline, motivation, ability of principal and teacher performance.